Etika Sosial dalam Al-Qur'an: Perspektif Ibnu Khaldun dan Kritik terhadap Pandangan Karl Marx tentang Agama - Ibnurusd Al Hafied, L.; Samsahudi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study provides an in-depth examination of the concept of social ethics as articulated in the Qur’an and the sociological thought of Ibn Khaldūn, while critically engaging with Karl Marx’s critique of religion from these perspectives. Confronted with contemporary social challenges such as structural inequality and moral disintegration, it is imperative to revisit ethical values rooted in the Islamic tradition. The Qur’an underscores principles of justice, solidarity, social responsibility, and equality as foundational to a just and prosperous social order. Concurrently, Ibn Khaldūn’s theory of ʿasabiyyah highlights the centrality of social cohesion in sustaining collective strength. In contrast to Marx’s portrayal of religion as an opiate that diverts attention from socio-economic realities, Islam positions faith as a moral force driving social transformation. Employing a qualitative methodology and textual analysis of the primary sources of these three intellectual traditions, this study concludes that integrating Islamic social ethics with Ibn Khaldūn’s framework offers a viable conceptual alternative to secular critiques of religion and contributes to the construction of an ethically grounded social paradigm for contemporary society